Gender-related peculiarities in the perception of patient care in copd patients - Yeryomenko, Galyna; Bezditko, Tetyana (Харківський національний медичний університет, 2025)
The nursing profession is one of the key professions in the healthcare system, as nurses ensure continuity of care, support patients and implement ethical principles in medicine. Despite thehigh importance of this activity, the nursing profession has historically been perceived as ‘feminine’. According to the World Health Organisation, about 90% of nursing staff are women. This gender imbalance not only reflects socio-cultural stereotypes, but also determines the characteristics of professional interaction, career development and the distribution of roles in the medical environment. At the same time, modern nursing practice requires consideration of the gender characteristics of patients themselves, as gender can influence the course of disease, response to treatment, stress levels, and perceptions of care. It is suggested that nurses focus on the individual needs of each patient, regardless of their gender, age orsocial status, viewing care as a conscious professional act based on the ethics of responsibility, empathy and gender sensitivity.
Keywords: gender-related peculiarities; patient care; COPD; 2025а